Best practice of ethical leadership among the academic administrators in Islamic tertiary education institution: academic staff’s perceptions - Salleh, Mohamad Johdi; Tiyunin, Zenita Arryani (Centre for Promoting Ideas, USA, 2014)
The purpose of the study is to investigate the best practice of Ethical Leadership among the academic administrators in Islamic Tertiary Education Institution as perceived by academic staff. This study is using a validated questionnaire that was developed by Kalshoven, Den Hartog & De Hoogh known as “Ethical Leadership at Work Questionnaire” (ELW). It is to measure the seven dimensions of ethical leader behaviour which comprises of ethical leadership scale, namely, fairness, integrity, ethical guidance, people orientation, power sharing, role clarification and concern for sustainability (Kalshoven, et al., 2011). The study involved 262 academic staffs from several kulliyyahs and centres of the International Islamic University Malaysia (IIUM), Kuala Lumpur. The data collected from the survey were analysed using the Statistical Package for the Social Science (SPSS) version 20.0. The result of the study shows that ‘role clarification’ has the highest mean score of 3.73, followed by ‘integrity’ with mean score 3.60, and, third highest scored practiced by the academic administrators was ‘concern for sustainability’ with mean 3.42. It is hoped that the findings in this study will contribute and encourage the tertiary education institution to improve further in its organization especially which is related to the academic administrators’ practice on ethical leadership behaviour. The impact will be huge throughout the world as can be seen as a world class university striving towards the vision and mission in enhancing the quality ummah in the era of globalization.